AhR mediates an anti‐inflammatory feedback mechanism in human Langerhans cells involving FcεRI and IDO. Issue 11 (10th May 2017) - Koch, S.; Stroisch, T. J.; Vorac, J.; Herrmann, N.; Leib, N.; Schnautz, S.; Kirins, H.; Förster, I.; Weighardt, H.; Bieber, T.
Abstract: Background: Aryl hydrocarbon receptor (AhR), an important regulator of immune responses, is activated by UVB irradiation in the skin. Langerhans cells (LC) in the epidermis of patients with atopic dermatitis (AD) carry the high‐affinity receptor for IgE, FcεRI, and are crucially involved in the pathogenesis of AD by inducing inflammatory responses and regulating tolerogenic processes. Objectives: We investigated AhR and AhR repressor (AhRR) expression and functional consequences of AhR activation in human ex vivo skin cells and in in vitro ‐generated LC. Methods: Epidermal cells from healthy skin were analyzed for their expression of AhR and AhRR. LC generated from CD34 + hematopoietic stem cells (CD34LC) were treated with the UV photoproduct and AhR ligand 6‐formylindolo[3, 2‐b]carbazole (FICZ). Cell surface receptors, transcription factors, and the tolerogenic tryptophan‐degrading enzyme indoleamine 2, 3‐dioxygenase ( IDO ) were analyzed using flow cytometry and quantitative PCR. Results: Epidermal LC and CD34LC express AhR and AhRR. AhR was also found in keratinocytes, which lack AhRR. AhR activation of LC by FICZ caused downregulation of FcεRI in CD34LC without affecting their maturation. AhR‐mediated regulation of FcεRI did not involve any known transcription factors related to this receptor. Furthermore, we could show upregulation of IDO mediated by AhR engagement. Conclusions: Our study shows that AhR activation by FICZ reduces FcεRI and upregulates IDO expression in LC. This AhR‐mediated anti‐inflammatory feedback mechanism may dampen the allergen‐induced inflammation in AD.